DASH cryptochrome 1, a UV‐A receptor, balances the photosynthetic machinery of Chlamydomonas reinhardtii. Issue 2 (30th July 2021) - Rredhi, Anxhela; Petersen, Jan; Schubert, Melvin; Li, Wei; Oldemeyer, Sabine; Li, Wenshuang; Westermann, Martin; Wagner, Volker; Kottke, Tilman; Mittag, Maria
Summary: Drosophila, Arabidopsis, Synechocystis, Homo (DASH) cryptochromes belong to the cryptochrome/photolyase family and can act as DNA repair enzymes. In bacteria and fungi, they also can play regulatory roles, but in plants their biological functions remain elusive. Here, we characterize CRY‐DASH1 from the green alga Chlamydomonas reinhardtii . We perform biochemical and in vitro photochemical analysis. For functional characterization, a knock‐out mutant of cry‐dash1 is used. CRY‐DASH1 protein is localized in the chloroplast and accumulates at midday. Although the photoautotrophic growth of the mutant is significantly reduced compared to the wild‐type (WT), the mutant has increased levels of photosynthetic pigments and a higher maximum photochemical efficiency of photosystem II (PS II). Hyper‐stacking of thylakoid membranes occurs together with an increase in proteins of the PS II reaction center, D1 and its antenna CP43, but not of their transcripts. CRY‐DASH1 binds fully reduced flavin adenine dinucleotide and the antenna 5, 10‐methenyltetrahydrofolate, leading to an absorption peak in the UV‐A range. Supplementation of white light with UV‐A increases photoautotrophic growth of the WT but not of the cry‐dash1 mutant. These results suggest a balancing function of CRY‐DASH1 in the photosynthetic machinery and point to its role as a photoreceptor for the UV‐A range separated from the absorption of photosynthetic pigments.